Exploring Reflective Practices for In-service English Language Teachers’ Professional Development - Bhandari, Bhim Lal (Journal of Research in Education, 2025)
Reflective practice helps teachers to enhance their professional development by critically evaluating their actions, sharing experiences, and building confidence through collaborative discussions with peers. This study aims to explore reflective practices for in-service English language teachers’ professional development. Narrative inquiry was employed as the research method, with semi-structured interviews to capture the participants’ lived experiences. Four English language teachers, teaching at the secondary level in Rupandehi, were purposefully selected from two public schools as participants. The data collected were analyzed using thematic analysis, which allowed for the identification of key patterns and insights related to reflective practices. The findings revealed that all participants consistently engaged in reflective practices within their classroom teaching, regularly adapting and modifying their teaching strategies to enhance and update their professional skills. Reflective practice also fosters continuous professional growth by encouraging teachers to evaluate their actions, collaborate with peers, and promote a culture of sharing and pedagogical improvement. These findings suggest that reflective practice plays a crucial role in ongoing professional development, allowing educators to refine their teaching techniques. The study provides valuable insights for teachers, supporting them in becoming proficient reflective practitioners and contributing to more effective teaching methods.